Metric competencies for biomedical librarians: results of a survey developed by the EAHIL Evaluation and Metrics group - Gómez-Sánchez, Alicia Fátima; Scotti, Valeria; De Silvestri, Annalisa; Ardita, Guise; Halling, T Derek; Chaleplioglou, Artemis (Journal of EAHIL, 2019)
The library profession continues to evolve and respond to user demands with both tools and services that support instruction and research. These changes typically lead to a need for increased librarian understanding and training. One such example is seen in the growing interest surrounding bibliometrics, altmetrics, and personal identifiers. Each of these serve as indicators of impact, and are becoming increasingly important in research. To more clearly identify and measure the current prevalence of each in the librarian profession, the EAHIL Metrics Group developed and disseminated a survey designed to capture current demand, and identify potential knowledge gaps where training would be beneficial. This publication presents the results of the survey and discusses pathways to attaining and providing increased expertise.